Respuesta :
-7c+9=c+1 (subtract c on both sides)
-8c+9=1 (subtract 9 on both sides)
-8c=-8 (divide by -8 on both sides to get c by its self)
c=1
your answer is 1.
-8c+9=1 (subtract 9 on both sides)
-8c=-8 (divide by -8 on both sides to get c by its self)
c=1
your answer is 1.
c = 1
-7c + 9 = c + 1
+7c +7c (combine light terms)
9 = 8c + 1
-1 -1 (do the math)
8 = 8c
_ _ (divide by 8 on both side)
8 8
1 = c
-7c + 9 = c + 1
+7c +7c (combine light terms)
9 = 8c + 1
-1 -1 (do the math)
8 = 8c
_ _ (divide by 8 on both side)
8 8
1 = c